Citigroup : restoring ethics and image before growth - Ratliff, Julie; Lee, David; O'Rourke, James S., 1946- (London : SAGE Publications Ltd, 2017)
The new CEO of Citigroup, Charles Prince, proposes a Five Point Ethics Plan in an attempt to change the ethics, culture and operations of the company. The plan is a response to significant regulatory scrutiny, paying out massive legal settlements and a Federal Reserve announcement requiring the company to refrain from mergers and acquisitions until it has cleaned up internal controls. His plan includes expanded training, enhanced focus on talent, balanced performance appraisals, improved communications and strengthened compliance controls. As current key executives leave the company and experts in ethics are skeptical, many wonder if Citigroup will be able to successfully communicate this program while it holds back on growth to implement this new culture.
Originally published in Ratliff, J., Lee, D., & ORourke, J. S. (2006). Citigroup: Restoring ethics and image before growth. 06-04. Notre Dame, IN: The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Citigroup (Firm); Financial institutions; Business ethics; Corporate culture; Organizational behavior